A polypyrrole/black-TiO2/S double-shelled composite fixing polysulfides for lithium-sulfur batteries. (1st September 2020) - Wu, Tong; Sun, Guiru; Lu, Wei; Zhao, Liping; Mauger, Alain; Julien, Christian M.; Sun, Liqun; Xie, Haiming; Liu, Jinghai
Abstract: The inhibition of the shuttle of lithium polysulfides (LiPSs) and enhancement of the electrical conductivity of the cathodes are desirable to improve the performance of lithium-sulfur batteries. In the present work, we report a cathode acting simultaneously as a highly efficient LiPSs immobilizer and sulfur host. It is composed of sulfur embedded inside a hollow sphere, the shell of which is made of hollow black TiO2 (b-TiO2 ) spherical nanoparticles. The particles of the composite are then coated with a polypyrrole (PPy) layer to form the active cathode element (b-TiO2 /S@PPy). The particular topology of the b-TiO2 layer provides enough space to alleviate the volume expansion of LiPSs. Equally, the PPy coating layer can not only improve the conductivity of the cathodes, but also restrain the shuttle of LiPSs by chemical adsorption. With the sulfur content of 59.6 wt% corresponding to a sulfur loading of 1.5–1.8 mg cm −2, the lithium-sulfur batteries with the b-TiO2 /S@PPy cathode exhibits a high initial discharge capacity (1374 mAh g −1 at 0.1C), a superior cycling stability (910 mAh g −1 after 200 cycles at 0.1C), and a good rate performance (725 mAh g −1 at 2C). Highlights: Kirkendall effect used to synthesize double-shelled PPy/black-TiO2 /S nanocomposites. The black-TiO2 shell formed of close-packed hollow spherical particles. Due to oxygen vacancies, the surface of TiO2 fixes the soluble polysufides. Specific capacity maintained at 910 mAh g-1 after 200 cycles at 0.1C. The composite shows remarkable performance as a cathode for Li–S batteries.